2008
DOI: 10.1002/cncr.23406
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and outcome of nephron‐sparing surgery for children with bilateral Wilms tumor

Abstract: BACKGROUND. Approximately 5% of children with Wilms tumor present with bilateral disease. The treatment challenge is to achieve a high cure rate while maintaining adequate long‐term renal function. The authors of this report assessed the feasibility and outcome of nephron‐sparing surgery in patients with bilateral Wilms tumor who were treated at a single institution. METHODS. A retrospective review was performed of all children who were treated at St. Jude Children's Research Hospital for synchronous, bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 28 publications
1
92
0
4
Order By: Relevance
“…The indication for RN in our study was in accordance of the study done by Fuchs et al (Presence of hilar tumor) [21]. In Davidoff et al study, they reviewed 12 patients with bilateral Wilm's tumor, 10 of them had bilateral simultaneous NSS, 1 had RN on one side (due to extensive tumor thrombus) with contralateral NSS, and 1 patient had bilateral RN (due to anaplastic histology and presentation with renal failure) [22].…”
Section: Discussionsupporting
confidence: 70%
“…The indication for RN in our study was in accordance of the study done by Fuchs et al (Presence of hilar tumor) [21]. In Davidoff et al study, they reviewed 12 patients with bilateral Wilm's tumor, 10 of them had bilateral simultaneous NSS, 1 had RN on one side (due to extensive tumor thrombus) with contralateral NSS, and 1 patient had bilateral RN (due to anaplastic histology and presentation with renal failure) [22].…”
Section: Discussionsupporting
confidence: 70%
“…Nephron-sparing surgery has been accepted as the treatment of choice for children with bilateral WT, with WT on a single kidney, or with WT and a disease of the contralateral kidney [2,3]. Several surgeons have reported their experience on NSS for localized WT [3,6] with good results.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies revealed significant postoperative morbidity, recurrence and mortality, even with partial nephrectomy for BWT. Because of significant postoperative morbidity, the management has evolved from partial nephrectomy to renal-sparing surgery (3,4).…”
Section: Discussionmentioning
confidence: 99%